The Effect of Digital Leadership and Human Capital Agility on Employee Performance through Work Engagement in Technology-Based Organizations - Daud Arifin (Brilliant International Journal Of Management And Tourism, 2026)
This study aims to examine the influence of Digital Leadership and Human Capital Agility on Work Engagement and Employee Performance in the context of digital transformation. Rapid technological developments require organizations to strengthen leadership capabilities, workforce adaptability, and employee engagement to maintain sustainable performance. This study employed a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze data collected from 250 respondents through a structured questionnaire. The proposed model was evaluated through measurement and structural model testing, including validity, reliability, coefficient of determination, and hypothesis testing. The findings indicate that all proposed relationships are positive and statistically significant. Digital Leadership positively influences Work Engagement (β = 0.371) and Employee Performance (β = 0.345), while Human Capital Agility has a positive effect on Work Engagement (β = 0.399) and Employee Performance (β = 0.200). Furthermore, Work Engagement significantly improves Employee Performance (β = 0.306). The structural model explains 38.3% of the variance in Work Engagement and 46.1% of the variance in Employee Performance, indicating a moderate explanatory power. Human Capital Agility emerges as the strongest predictor of Work Engagement, whereas Digital Leadership provides the greatest direct contribution to Employee Performance. These findings suggest that organizational performance in the digital era is influenced not only by effective leadership but also by employees’ adaptability and engagement. This study contributes to the literature by integrating leadership, agility, engagement, and performance within a single framework and offers practical implications for organizations seeking to improve employee performance through digital leadership development, workforce agility enhancement, and employee engagement initiatives.